THE SPACE-TIME WAVES AND CHARGE CONSERVATION LAW - A. A. Kurayev (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
It is shown that charge conservation law, which is the fundamental postulate of the electromagnetic theory, follow from space-time waves conception.